バイク事故による橈骨遠位端骨折に合併した月状骨脱臼の1例(Lunate dislocation with distal radius fracture following a motorcycle accident: a case report). Issue 2 (18th February 2021) - (Akihiro Kato), 加藤 明裕; (Makoto Fukuta), 福田 誠; (Yohei Kawaguchi), 川口 洋平; (Takahiro Goshima), 五島 隆宏; (Asako Matsushima), 松嶋 麻子
ABSTRACT: Lunate dislocation is a palmar dislocation of the lunar bone caused by high–energy trauma such as falling from a motorcycle. It is a rare injury often misdiagnosed on initial examination. Median nerve paralysis or ischemic necrosis of the lunar bone may occur if not treated quickly. We report a case of lunate dislocation with distal radius fracture after a motorcycle accident. A 27–year–old man driving a motorcycle collided with a car and fell off. He complained of left wrist pain. Physical examination revealed no head or trunk trauma. He was diagnosed as having left lunate dislocation with distal radius fracture, right thumb metacarpal fracture and right capitate bone fracture by simple X–ray/CT examination. Open dislocation reduction and internal fixation were performed on the left wrist joint on the day of injury and on the right hand on the following day. He was discharged without complications on the ninth hospital day. The lunate dislocation was diagnosed and treated at an early stage, leading to a good outcome without complications. When diagnosing lunate dislocation, attention must be paid to the characteristic injury mechanism of severe wrist dorsiflexion and disorder of the carpal bone arrangement on simple X–ray images of the wrist joints. 要旨: 月状骨脱臼はスノーボードの転倒やバイクの交通事故の際に，手関節の強制背屈により生じた月状骨の掌側脱臼である。迅速に治療されない場合，合併症として正中神経麻痺や月状骨の虚血性壊死が起こるが，月状骨の脱臼は発生頻度が低く，救急外来では見逃されやすい外傷である。今回，バイク事故により橈骨遠位端骨折に合併した月状骨脱臼の1例を経験したので報告する。症例は27歳の男性。バイクで直進中に右折する自動車と衝突し，ボンネットに乗り上げた後，落下した。頭部，体幹に特記すべき外傷はなく，左手関節の変形と橈骨遠位部に圧痛を認め，右母指中手骨にも圧痛を認めた。単純X線およびCT検査で左橈骨遠位端骨折と尺骨茎状突起骨折，左月状骨脱臼および右母指中手骨骨折，右有頭骨骨折と診断した。受傷当日，左手に対し観血的脱臼整復固定術を施行し，入院2日目には右手に対する観血的整復固定術を施行した。入院9日目に合併症なく退院した。本症例では月状骨脱臼を早期に診断し，治療したことで合併症なく，良好な転帰につながった。月状骨脱臼は早期に診断し，整復することが良好な機能予後を得るために重要であり，交通外傷の初療を担当する救急医が注意するべき外傷である。月状骨脱臼を示唆する，手関節の高度背屈という特徴的な受傷機転と，単純X線像における手根骨の配列の乱れについて日頃から注意を払うことが重要と考える。